Theoretical Calculations of Rate Constant of Electron Transfer Across N3/TiO2 Sensitized Dye Interface Solar Cell - Al-agealy, H.J.M; Al-Hakany, J. S. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The rate of electron transfer from N3 sensitized by dye to TiO2 semiconductor in variety solvent have been calculated as a function of reorientation energy effective free energy , volume of semiconductor , attenuation and lattice constant of semiconductor .       A very strong dependence of the electron transfer rate constant on the reorientation and effective free energy .Results of calculation indicate that TiO2 is available to use with N3 dye .Our calculation results show that a good agreement with experimental result